2014
DOI: 10.1007/s00421-014-2879-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptations in skeletal muscle, adipose tissue, and whole-body oxidative capacity in response to resistance training

Abstract: Despite significant increases in VO2 peak, fat oxidation, and lean mass following resistance training, the total effect on gene expression and enzyme activity linked to oxidative metabolism was moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 47 publications
7
22
0
Order By: Relevance
“…In the current study, CS activity increased following RET, however, this increase was not statistically significant (Figure 2A). This is in agreement with most(1, 28, 34, 35, 37)but not all (33) reports of the impact of chronic RET on skeletal muscle oxidative capacity. In the cohort of participants studied here, CS activity was not correlated with maximal coupled mitochondrial respiration (P) before (Figure 2B) or after (Figure 2C) RET, suggesting that changes in mitochondrial respiratory capacity with RET are not accompanied by concurrent alterations in markers of skeletal muscle oxidative capacity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, CS activity increased following RET, however, this increase was not statistically significant (Figure 2A). This is in agreement with most(1, 28, 34, 35, 37)but not all (33) reports of the impact of chronic RET on skeletal muscle oxidative capacity. In the cohort of participants studied here, CS activity was not correlated with maximal coupled mitochondrial respiration (P) before (Figure 2B) or after (Figure 2C) RET, suggesting that changes in mitochondrial respiratory capacity with RET are not accompanied by concurrent alterations in markers of skeletal muscle oxidative capacity.…”
Section: Discussionsupporting
confidence: 92%
“…It has been postulated that increased content of mitochondrial proteins is drivenby increased transcriptional regulation of mitochondrial biogenesis (14). Similar to previous reports(1), we did not see a pronounced increase in the expression of mRNA”s involved in mitochondrial biogenesis (COX18, MFN1, NDRG2, PPARGC1A (PGC1α) and TFAM), assessed 3 days after the last day of RET. It should be noted that marked improvements in aerobic capacity can be see without chronic increases (31), or even a decrease (16) in markers of mitochondrial biogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, an 8-week resistance exercise program did not alter PGC-1a or FNDC5 mRNA in muscle of young healthy adults 64 . In addition, 12 weeks of resistance training did not alter PGC-1a splice variant1 mRNA, and it did not change the FNDC5 mRNA in muscle in untrained young females 19 .…”
Section: Reporting Of the Outcomesmentioning
confidence: 80%
“…For example, a study by Raschke et al [62] indicated that FNDC5 mRNA expression was not altered in muscle biopsies from human endurance and strength training studies, and questioned whether the beneficial effects of irisin in mice can be translated to humans. Another consideration is that although there are many studies regarding the effects of exercise on human serum irisin levels [63][64][65][66], these studies make conflicting claims about the relationship between circulating irisin levels and exercise [67][68][69][70][71][72][73][74]. Many studies used commercially available ELISA kits to examine serum irisin levels that caused Albrecht et al [59] to call into question the accuracy of these data, because when they used western blot analysis with four different antibodies and a sensitive detection system to examine circulating irisin in humans or several animal species, they found unchanged serum irisin levels before and after exercise.…”
Section: Irisinmentioning
confidence: 99%